Feasibility of continuous bronchoscopy during exercise in the assessment of large airway movement in healthy subjects - Williams, Zander J.; Orton, Christopher M.; Garner, Justin L.; Chan, Ley T.; Tana, Anand; Shah, Pallav L.; Polkey, Michael I.; Semple, Thomas; Hull, James H. (Journal of applied physiology (1985), 2024)
This study demonstrates that large airway movement can be visualized with bronchoscopy undertaken during vigorous exercise. This approach does not require sedation and permits characterization of the behavior of the large airways and the tendency toward collapse during upright, ambulatory exercise. In healthy individuals, the response pattern of the large airways during exercise appears to differ markedly from the pattern of airway closure witnessed during forced expiratory maneuvers, assessed via imaging. Excessive dynamic airway collapse (EDAC) is a recognized cause of exertional dyspnea arising due to invagination of the trachea and/or main bronchi. EDAC is typically assessed by evaluating large airway movement with forced expiratory maneuvers. This differs from the respiratory response to exercise hyperpnea. We aimed to evaluate large airway movement during physical activity, with continuous bronchoscopy during exercise (CBE), in healthy subjects and compare findings with resting bronchoscopic maneuvers and imaging techniques. Twenty-eight individuals were recruited to complete two visits including treadmill-based CBE, to voluntary exhaustion, and cine magnetic resonance imaging (MRI) with forced expiratory maneuvers at rest. Twenty-five subjects [aged 29 (26–33) yr, 52% female] completed the study ( n = 2 withdrew before bronchoscopy, and one was unable to tolerate insertion of bronchoscope). The majority (76%) achieved a peak heart rate of >90% predicted during CBE. The procedure was prematurely terminated in five subjects ( n = 3; elevated blood pressure and n = 2; minor oxygen desaturation). The CBE assessment enabled adequate tracheal visualization in all cases. Excessive dynamic airway collapse (tracheal collapse ≥50%) was identified in 16 subjects (64%) on MRI, and in six (24%) individuals during resting bronchoscopy, but in no cases with CBE. No serious adverse events were reported, but minor adverse events were evident. The CBE procedure permits visualization of large airway movement during physical activity. In healthy subjects, there was no evidence of EDAC during strenuous exercise, despite evidence during forced maneuvers on imaging, thus challenging conventional approaches to diagnosis. NEW & NOTEWORTHY This study demonstrates that large airway movement can be visualized with bronchoscopy undertaken during vigorous exercise. This approach does not require sedation and permits characterization of the behavior of the large airways and the tendency toward collapse during upright, ambulatory exercise. In healthy individuals, the response pattern of the large airways during exercise appears to differ markedly from the pattern of airway closure witnessed during forced expiratory maneuvers, assessed via imaging.